Pendekatan Sinematografi dalam Perwujudan Visualisasi Tradisi Pacu Jawi - Tedy Wiraseptya; Stefvany Stefvany (SENTRI: Jurnal Riset Ilmiah, 2026)
Pacu Jawi is a traditional Minangkabau cultural practice characterized by dynamic movement, emotional intensity, and a close relationship between humans and the agrarian landscape. However, audiovisual representations of Pacu Jawi often remain limited to surface-level documentation, without conveying deeper cultural meanings. This study highlights a novel contribution by examining cinematography as a strategic approach for cultural representation in documentary video, rather than treating documentary as merely an archival record. Using a qualitative descriptive method, the research analyzes a Pacu Jawi documentary through shot composition, camera angles, movement, lighting, color, and visual rhythm. The findings show that wide shots establish cultural space and environmental identity, while close-ups emphasize emotional expression and human–animal interaction. Dynamic handheld and tracking movements enhance immersion, supported by natural lighting and warm tones that reinforce authenticity. The study concludes that cinematographic strategies transform documentary video into an active medium for communicating Pacu Jawi’s traditional values. This research contributes academically to visual communication studies and practically informs filmmakers and cultural institutions in preserving local traditions.